STRATEGI PUBLIC RELATIONS (PR) MOMIS BAKERY DALAM MEMVIRALKAN PRODUK ANDALANNYA - Ghassani, Rizqi; Fitriawati, Diny (KOMUNIKA BANGSA, 2024)
Maximum use of the internet will have an impact on the success of marketing a product. Even though the product in question is still relatively new, accuracy in utilizing the vastness of the internet can provide maximum profits for product sales to occupy the top position. The ability to do this can be obtained by using features that are spread through social media applications that are scattered throughout the internet. As the backbone that unites communication media, both personal and public, the internet must be utilized optimally for various purposes. One of them, business goals. As was done by Momis Bakery which went viral with public interest in the products it makes. On that basis, this research was carried out with the aim of uncovering viral phenomena as a public relations strategy for marketing Momis Bakery products on social media. As a means, this research uses qualitative research methods with interpretive descriptive research which seeks to uncover the background of the phenomenon behind the virality that occurs. The research results prove that the use of media combined with skills in carrying out public relations functions helps elevate Momis Bakery to the top position. Keywords: Internet, public relations, viral, social media, products